Effect of Cationic Starch- CMC Self-assembly Layers on Recovered Fibers of Neutral Sulfite Semi-chemical Pulp and Resultant Paper Properties - Hamid reza Rodi (Regional Information Center for Science and Technology (RICeST), 2018)
Improvement the strength properties of papers made from recycled fibers is of important aims in papermaking industries. Current researches revealed that higher retention of strength induced additives through alternative absorption of polymers having opposite charge is one of promising approaches to obtain such purpose. In this study, treatment of fibers prepared from neutral sulfite semi-chemical papers with cationic starch and anionic CMC was conducted in pH~7, pH~10 and 0.001 M NaCl salty suspension. Then, fibers water retention value and zeta potential was measured. Standard handsheets with 60±3 g/m2 basis weight were made from untreated and treated pulps. The results have shown that fibers WRV significantly increased by absorbing of these two water-loving polymers. Consecutive changes of zeta potential confirmed charge reversion of fibers surface and sequential absorption of couple polymers. Scanning electron micrographs prepared from the samples of untreated and treated papers presented new variations in amount of fibers bend area due to the larger absorption of these two reinforcement polymers. Moreover, considerable development in paper mechanical characteristics (tensile, burst and tear indices) proved the success of high absorption of applied bio-polymers.